OTU-17 Methylation panel in the assessment of clinical response to the radio-frequency ablation for barrett's oesophagus. (June 2019) - Januszewicz, Wladyslaw; Waldock, William; Subhash, Vinod Vijay; Fernando, Daniel; Bartalucci, Giorgio; Leeman, Emma; Chettouh, Hamza; Miremadi, Ahmad; O'Donovan, Maria; Fitzgerald, Rebecca C; di Pietro, Massimiliano
Abstract : Introduction: After radiofrequency ablation (RFA) for Barrett's oesophagus (BE) random biopsies at the gastro-oesophageal junction (GOJ) are taken to detect residual intestinal metaplasia (IM). It's debatable whether IM at the GOJ is a reliable marker of residual disease since it is subjective and patchy in nature. We have previously shown that methylation panel is accurate in identifying IM within the oesophageal tissue. We aimed to investigate whether a methylation panel in oesophageal and GOJ biopsies can be used to risk-stratify patients after RFA. Methods: We analyzed paraffin-embedded 4-quadrant BE and GOJ biopsies from patients undergoing RFA treatment with at least 2 post-RFA follow-up endoscopies. The IM extent was classified using a 4-tier system (IM-Score) based on number of glands with goblet cells (1, 2–5 or >5 glands) and number of biopsies with IM (0=no IM, 1=focal, 2=moderate and 3=extensive). Promoter methylation at 3 genes (ZNF345, TFP12, ZNF569) was assessed by Methylight and a mean value was generated (Meth-Score). Methylation levels where compared using one-way ANOVA and Wilcoxon test, where appropriate. Results: We included 45 patients, who achieved endoscopic remission after RFA. The pre-RFA grades included: non-dysplastic BE (NDBE) (24.4%), low-grade dysplasia (LGD) (31.1%), high-grade dysplasia/intramucosal carcinoma (HGD/IMC) (44.4%). Overall, the methylation levels correlated with the degree of dysplasia, with a Meth-Score of 40.5%, 63.0% and 80.6% in NDBE, LGD, HGD/IMC, respectively ( P <0.001). Hundred-and-five post-RFA GOJ biopsy sets were analysed of which 87(82.9%) had IM-score of 0-1 and 18(17.1%) had IM score 2-3, with corresponding mean methylation levels of 2.4% and 35.5%, respectively ( P =0.018). In patients with GOJ-IM, who received RFA re-treatment, the Meth-Score decreased from 24% to 4.2% ( P =0.027) as presented in figure 1. Conclusions: The methylation panel can differentiate grades of dysplasia in Barrett's and significantly correlates with the extent of IM at the GOJ. We propose the Meth-Score as an objective measure of residual and recurrent disease following RFA. GOJ, gastro-oesophageal junction; IM, intestinal metaplasia; RFA, radio-frequency ablation.